Role Of Transportation Thein Supporting Sustainable Halal Tourism In Indonesia - Hadi Peristiwo (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2021)
The potential for the development of halal tourism in Indonesia is considered very promising and will become a business that many tourism businesses are interested in. This is in line with the increase in halal tourism from year to year. Transportation has an important role in supporting sustainable halal tourism. This journal's literature review will explore the role of transportation in sustainable halal tourism, the concept of transportation mode planning in sustainable halal tourism and discuss transportation challenges and problems for sustainable halal tourism in Indonesia. This journal review literature research method is carried out by searching for published articles on Sage, Elsivier Science and Taylor & Francis with the selected keywords, namely transportation, halal sustainable tourism, and tourism and hospitality. The search was carried out by limiting publications from 2010 - 2020. From the results of the literature search, it can be seen that transportation has an important role for sustainable halal tourism, because the key characteristic of tourists is mobility. Challenges and problems in sustainable halal tourism transportation services in Indonesia in general are still faced with problems of increasing safety, increasing smooth mobility and problems of service accessibility. Key words : transportation, sustainable halal tourism.